Successful Team Building - Quick, Thomas L. (New York Amacom, 1992)
Working in teams brings benefits to both team members and the organizations for which they work. In this do-it-yourself guide, the head of his own consulting firm shows how to motivate team members and build team commitment, deal with team conflict, use creativity in problem solving, and evaluate and reward team players.
Keywords: Teams in the workplace -- BUSINESS & ECONOMICS -- Workplace Culture. -- BUSINESS & ECONOMICS -- Corporate Governance